Thyroid Stem Cells But Not Differentiated Thyrocytes Are Sensitive to Slightly Increased Concentrations of Heavy Metals - Gianì, Fiorenza; Masto, Roberta; Trovato, Maria Antonietta; Franco, Annarita; Pandini, Giuseppe; Vigneri, Riccardo (Frontiers in Endocrinology, 2021)
Thyroid cancer incidence is markedly increased in volcanic areas where residents are biocontaminated by chronic lifelong exposure to slightly increased metals in the environment. Metals can influence the biology of living cells by a variety of mechanisms, depending not only on the dose and length of exposure but also on the type and stage of differentiation of target cells. We explored the effect of five heavy metals (Cu, Hg, Pd, W and Zn) at nanomolar concentrations (the biocontamination level in residents of the volcanic area in Sicily where thyroid cancer is increased) on stimulating the proliferation of undifferentiated (thyrospheres) and differentiated human thyroid cells. Thyrosphere proliferation was significantly increased after exposure to each individual metal and a greater stimulating effect was observed when a mixture of the examined metals was used. No effect was seen in differentiated thyrocytes. For all metals, the dose-response curve followed a biphasic pattern that is typical of hormesis. Thyrosphere growth concerned the size rather than number, except with the metal mixture. An altered morphology was also observed in metal-treated thyrospheres. Metal-induced proliferation was due to activation of the ERK1/2 pathway, as confirmed by growth inhibition when ERK1/2 signaling was blocked. These studies show that stem/precursor thyroid cells are sensitive to small increases in environmental metal concentrations that are harmless for differentiated thyrocytes.